2017
DOI: 10.1136/bmjopen-2017-016009
|View full text |Cite
|
Sign up to set email alerts
|

Web-based self-management support for people with type 2 diabetes (HeLP-Diabetes): randomised controlled trial in English primary care

Abstract: ObjectiveTo determine the effectiveness of a web-based self-management programme for people with type 2 diabetes in improving glycaemic control and reducing diabetes-related distress.Methods and designIndividually randomised two-arm controlled trial.Setting21 general practices in England.ParticipantsAdults aged 18 or over with a diagnosis of type 2 diabetes registered with participating general practices.Intervention and comparatorUsual care plus either Healthy Living for People with Diabetes (HeLP-Diabetes), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 44 publications
2
83
0
4
Order By: Relevance
“…The majority of previous studies with ICT have demonstrated positive changes in health status, and sometimes increase quality of life in patients with crhonic diseases [22] which corroborates a study that we selected [19]. Also, describing that ICT increased the opportunities to patients for accessing information that disease's self-management [15], [16], [17], [18], [19], the management of symptoms, the identification of exacerbations and therapeutic management [15], [16], [19].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The majority of previous studies with ICT have demonstrated positive changes in health status, and sometimes increase quality of life in patients with crhonic diseases [22] which corroborates a study that we selected [19]. Also, describing that ICT increased the opportunities to patients for accessing information that disease's self-management [15], [16], [17], [18], [19], the management of symptoms, the identification of exacerbations and therapeutic management [15], [16], [19].…”
Section: Resultssupporting
confidence: 82%
“…We verified that the ICT's were identical in the different studies, the web intervention provided throughout the informative platforms and of registration as well as of e-learning where the more evidenced. It was possible to identify that the ICT's have positive effects in the patients with chronic diseases, which was verified that these have effects in the promotion of self-care and in selfmanagement of their health [15], [16], [17], [18], [19]. One of the results of the studies was the improvement of the overall increase of the patient's heath status, linked with a bigger knowledge and information about the control of symptoms and therapeutic regime [16] that allowed a better selfmanagement of their condition, decreasing the visits to the hospital [15].…”
Section: Resultsmentioning
confidence: 79%
“…In terms of study retention, we found that MSM and TGW in the Offline group who were not offered an online tool to self‐manage their appointments and communicate any concerns with study staff in between scheduled study visits did more poorly than those who were offered. Online self‐management represents a promising strategy for preventing and treating chronic conditions, such as diabetes and mental health disorders, as individuals are empowered to actively identify challenges and solve problems associated with their health conditions . Many ongoing studies are exploring the online self‐management concept for HIV testing, PrEP and ART use among MSM and TGW .…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 and Table 5 summarises data related specifically to SES and disparity, including the theory behind the SM intervention (or study question for participation/attrition studies), intervention description, SES adaptations made, SES status of population, results in relation to SES, dropout rates and overall impact on SES disparity. Related papers were retrieved to provide additional data about the population or intervention as needed [31][32][33][34][35][36][37][38]. Quality analysis was undertaken using the Joanna Briggs Institute checklists [30] for randomised controlled trials (RCTs) and observational studies, and the Sun/ Oxman criteria [27,28] for subgroup analyses.…”
Section: Data Abstractionmentioning
confidence: 99%